Adiponectin and Atherosclerosis in Rheumatoid Arthritis - Patrick H. Dessein; Linda Tsang; Ahmed Solomon; Angela J. Woodiwiss; Aletta M. E. Millen; Gavin R. Norton (Hindawi Limited, 2014)
In the present study, we examined the potential impact of adiponectin on carotid ultrasound determined atherosclerosis in 210 (119 black and 91 white) RA patients in mixed regression models. Total adiponectin concentrations were smaller in patients with compared to those without the metabolic syndrome (MetS) defined waist criterion (median (range) = 6.47 (1.23-34.54) versus 8.38 (0.82-85.30) ng/mL, P=0.02, resp.); both total and high molecular weight (HMW) adiponectin concentrations were larger in patients with compared to those without joint deformities (7.97 (0.82-85.30) and 3.51 (0.01-35.40) versus 5.36 (1.29-19.49) and 2.34 (0.01-19.49) ng/mL, P=0.003 and 0.02, resp.). Total and HMW adiponectin concentrations were associated with carotid artery plaque in patients with MetS waist (odds ratio (95% CI) = 0.87 (0.76-0.99) and 0.92 (0.85-0.99) per 1-standard deviation increment, P=0.02 for both) and those without joint deformities (odds ratio (95% CI) = 0.94 (0.88-0.99) and 0.94 (0.89-0.99), P=0.03 for both). Plaque prevalence was lower in patients without compared to those with joint deformities (23.4% versus 42.6, P=0.004 in multivariable analysis). In RA patients with abdominal obesity or no clinically evident joint damage, adiponectin concentrations are reduced but nevertheless associated with decreased carotid atherosclerosis.